2008
DOI: 10.1243/17543371jset9
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and analysis of grip force during a golf shot

Abstract: DOI: 10.1243/17543371JSET9Abstract: In this study, grip force was measured during a standard golf tee shot using two different measurement techniques. The first utilized a matrix-type thin-film sensor applied to a golf grip, from which total grip force could be readily determined. The second method involved 31 individual thin-film force sensors strategically placed on two golf gloves, allowing the force output of specific regions of the hands to be measured. Twenty golfers of varying ability participated in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…However, it is important to note that in [35] only a video-based grip classification scheme was used which did not consider the biomechanics associated with different pencil grip shapes. Finally, studies of grip forces associated with golf swings have shown that each player deploys a repeatable grip force profile that is distinct from that of other players [36][38]. Our finding corroborates the general conclusion of these studies that a high level of intra-participant grip kinetic repeatability tends to accompany a well-learned manual motor activity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, it is important to note that in [35] only a video-based grip classification scheme was used which did not consider the biomechanics associated with different pencil grip shapes. Finally, studies of grip forces associated with golf swings have shown that each player deploys a repeatable grip force profile that is distinct from that of other players [36][38]. Our finding corroborates the general conclusion of these studies that a high level of intra-participant grip kinetic repeatability tends to accompany a well-learned manual motor activity.…”
Section: Discussionsupporting
confidence: 87%
“…Hence, kinetic variation across individuals is not unexpected. Such variation has also been noted with other motor skills such as golf swings [36][38].…”
Section: Discussionmentioning
confidence: 60%
“…Participants were instructed to maintain an intensity equivalent to the one that they would produce under real match conditions. Grip strength was measured with a cylindrical dynamometer (circumference ¼ 110 mm) equipped with a pressure sensitive pad (Tekscan 9801) (Komi et al 2008). Subjects were seated with an elbow flexed at 908.…”
Section: Methodsmentioning
confidence: 99%
“…[7,12,22]. Each of the chosen features represent a different aspect of grip kinetics, namely, the grip shape (NCC), the overall grip force (TAF), and the spread of the grip force (TFIQR).…”
Section: Feature Extractionmentioning
confidence: 99%